2017
DOI: 10.1186/s12940-017-0262-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation at birth in relation to in utero arsenic exposure and the associated health in later life

Abstract: BackgroundIn utero arsenic exposure may alter fetal developmental programming by altering DNA methylation, which may result in a higher risk of disease in later life. We evaluated the association between in utero arsenic exposure and DNA methylation (DNAm) in cord blood and its influence in later life.MethodsGenome-wide DNA methylation in cord blood from 64 subjects in the Taiwanese maternal infant and birth cohort was analyzed. Robust regressions were applied to assess the association of DNA methylation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 64 publications
1
23
0
1
Order By: Relevance
“…However, this is difficult to assess, given that enhancers were only interrogated by the most recent MethylationEPIC array, and previous genome-wide studies with EDCs have used the Human Methylation450 array that has fewer probes in enhancer regions [7,58,59]. It is possible that as more studies with environmental exposures are done on arrays that more completely assess enhancer methylation, enrichment at enhancer regions will be more commonly found.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is difficult to assess, given that enhancers were only interrogated by the most recent MethylationEPIC array, and previous genome-wide studies with EDCs have used the Human Methylation450 array that has fewer probes in enhancer regions [7,58,59]. It is possible that as more studies with environmental exposures are done on arrays that more completely assess enhancer methylation, enrichment at enhancer regions will be more commonly found.…”
Section: Discussionmentioning
confidence: 99%
“…Larger amounts of arsenic are known to be associated with gastrointestinal disturbance and other adverse effects (6)(7)(8). These adverse health hazards could include cancer or other health disorders (5,7,(9)(10)(11)(12). Specifically, exposure to arsenic by ingestion is known to be associated with liver, lung, kidney, and bladder cancer (see reference 13).…”
mentioning
confidence: 99%
“…Most of the studies have only single timepoint epigenetic measurement taken either early in life with a particular exposure or the later in life with the outcomes. For example, Kaushal et al reported that prenatal arsenic exposure leads to the changes of five CpGs methylation in cord blood which were in the pathways related to cardiovascular diseases; also, the changed DNA methylation was associated with low-density lipoprotein of the children at the age of 2 to 14 years [30]. Additionally, prenatal particulate matter (PM) 2.5 exposure was associated with hypermethylation of children’s nasal epithelia glutathione S-transferase P1 ( GSTP1 ) gene that is also inversely associated with reduced children’s lung function in early childhood [56].…”
Section: Epigenetic Toxicitymentioning
confidence: 99%